A organização espacial de Mata/RS: reestruturação produtiva no seu espaço rural - Moraes, Fernanda Dalosto (2009)
The agricultural and livestock activities have been passing through important transformations, having the understanding of the rural space constantly reviewed to understand the territorial dynamics. It can be said that the field is re-drawn and it is reorganized at the same time new economical factors show up, restructuring the space cuttings. In that context, the work had as study focus the territorial unit of Mata/RS, due to the importance of the primary activities in its social and spatial organization, once these are constituted in the foundation of its economical source. Following this reasoning line, the specific objectives of the research sought: (a) to verify the evolution and the current situation of the agriculture and of the livestock in the Municipal district, in study in the temporary scale 1970 - 2007; (b) to analyze the different productive chains and their importance as restructural agents in the organization of the rural space and in the local and regional economical development; (c) to demonstrate the new agricultural activities of production, the alternatives of income in the agricultural establishments, the processes of improvement of the products in the Municipal district and its influence in spatial arrangements and in local economy and (d) to evaluate the modernization degree presented by the agricultural activities in the territorial unit in study. Methodologically, the research accomplished, initially, further analysis of the theoretical matrix regarding the thematic in analysis. Later, collections of data were elaborated in primary sources (field work) and in secondary sources, through data of the agricultural censuses (IBGE) and of FEE. The field work took place through interviews, which were subsidized by questionnaires that assisted the different selected informers. These were addressed the rural proprietors; to the public organs as the Municipal Department of Agriculture, Union of the Rural Workers, EMATER and to the industries' owners for the improvement of Mata. As final consideration, it's pointed out that the productive section of Mata is re-organizing front to the new dynamics imposed by capital, through traditional productive chains as Beef Cattle, rice, tobacco, soy and corn, which seek, through a modern production, to improve the quality of its products and, consequently, to interfere in the local/regional market. Besides this productive reorganization, the dynamics of the rural space is also due to the revitalization of the milk chain and the insert of new productive chains that boost the local economy. The new economical factors are represented by the cultivation of walnuts, valorization of the cachaça stills (sugarcane brandy), rural tourism and, in some rural establishments, the presence of vegetable and fruit grangers. At the same time, other activities can be found, such as carpentry, furniture factory, museum, among others, which seek to add value to the family agriculture. It is emphasized that the spatial organization of Mata is due to reflexes of the different developed agricultural activities, once it is that section that moves the urban space. In that way, the rural space is the fundamental element to promote the local/regional development of the municipal district.